75 Is Cerebral Autoregulation Altered in Ageing? A Review. (6th February 2020) - Perez-Denia, L; Claffey, P; Kenny, R A; Finucane, C
Abstract: Introduction: Cerebral autoregulation (CA) ensures constant cerebral blood flow (CBF) in the face of blood pressure (BP) disturbances. While CA impairment is often implicated in the aetiology of age-related disorders e.g. falls, syncope, and brain ageing, there is conflicting evidence on the effect of normal or healthy ageing on cerebral autoregulation. Here we present results of a review investigating the effect of ageing on CA. Methods: A search was performed in Pubmed using the search terms "cerebral autoregulation" AND ("ageing" OR "age" OR "older" OR "elderly"). Studies were included if they were human studies in English assessing CA in healthy volunteers (free from disease) in which the effect of ageing on CAR was studied. Exclusion criteria included non-human studies, diseased cohorts and studies not measuring CA. Results: 26 studies (n=1326 total participants, age range 12-88) meeting the inclusion/exclusion criteria were identified. Significant heterogeneity was noted in applied methodologies with 88% of studies using static and 53% using dynamic protocols to measure CA. Transcranial Doppler (88%) and Near Infrared Spectroscopy (NIRS) (11%) were the most commonly used. Transfer function analysis (TFA) (38%), the Autoregulatory Index (ARI) (15%), and wavelet analysis (11%) were used to derive CA metric. The majority of studies suggested that CA is preserved (n=15) with ageing. However, a smaller number of studies (n=7) noted that CA is impaired or altered with ageing. Conclusions: There is a paucity of literature examining the relationship between CA and chronological ageing, with 60 per cent of studies reviewed suggesting that CA is preserved. Current hypotheses suggest that preservation of CA with ageing serves as a 'reserve' to compensate for impairment of other systems. Future work should investigate the role of impaired CA as potential biomarker of biological ageing.